A Facility Location and Allocation Model for Cooperative Fire Services - Jinke Ming; Jean-Philippe P. Richard; Jiping Zhu (IEEE Access, 2021)
Designing efficient urban fire service systems is of crucial importance as prompt responses to emergencies and accidents can drastically reduce property loss and mortality. To achieve these goals, holistic location-allocation models for cooperative fire services must consider multiple factors, such as fire station size, vehicle quantity, vehicle type, response time, service reliability, and traffic condition. This paper proposes a mixed-integer linear program model that takes these factors into account by using two coverage metrics: one related to vehicle coverage, indicating service reliability, and the other related to time coverage, describing service accessibility. Integrating these two metrics, a full or partial time and vehicle coverage (FPTVC) standard is obtained that characterizes the efficiency of response of cooperative fire services. A case study and multiple sensitivity analyses based on historical data from Hefei (China) are performed to demonstrate the relationships between vehicle coverage proportion, time coverage rate, fire station number, fire engine quantity, FPTVC, and total budget. The solutions obtained are further analyzed using GIS-based maps, which validate that the proposed model can help develop enhanced fire service systems designs.